Case Report: Molecular Features and Treatment Options for Small Bowel Adenocarcinoma - Cordova-Delgado, Miguel; Pizarro, Gonzalo; Pinto, Mauricio P.; Herrera, Maria Elisa; Garrido, Marcelo (Frontiers in Oncology, 2021)
Small bowel adenocarcinoma (SBA) is a rare malignancy characterized by poor prognosis. Recent efforts have sought to elucidate the genetic landscape and the molecular drivers behind this disease. Herein, we report the main molecular alterations in two metastatic (stage IV) SBA patients. Interestingly, one of them had gene alterations that affected signaling pathways previously described for SBA. However, a second patient displayed previously unreported alterations in this particular tumor type. Based on these findings we discuss potential treatment options for patients affected by this rare, aggressive disease.